SARS-CoV-2 complicated by transverse myelitis - Finsterer, Josef (Jour Med Resh and Health Sci, 2021)
With interest we read the article by Shahali et al. about a 63yo male with COVID-19 who experienced transverse myelitis 4d after clinical onset of an infection with SARS-CoV-2 [1].